Promoting Behavioral Variability in Individuals With Autism Spectrum Disorders: A Literature Review. (September 2014) - Wolfe, Katie; Slocum, Timothy A.; Kunnavatana, S. Shanun
Repetitive behavior is a hallmark feature of autism spectrum disorders (ASD), and can have adverse consequences related to social stigma and low rates of skill acquisition. Basic research suggests that variability, or the extent to which one response differs from previous responses, is amenable to antecedent and consequence manipulations. This article describes the concept of variability, synthesizes the findings of 14 recent studies on interventions to increase the variability of behavior in individuals with ASD, and proposes preliminary guidelines for practitioners that focus on building response repertoires, implementing contingencies to produce and maintain variability, and incorporating prompts to vary responding.